CONTROL OF SEXUAL DEVIANT BEHAVIOR OF MALE INMATES IN CLASS I DETENTION CENTER LABUHAN DELI - Sirait, Santa Veronica; Anwar, Umar (Universitas Nusa Cendana, 2025)
Sexual deviant behavior often occurs in prisons and detention centers in Indonesia. This occurs due to several factors, such as limited fulfillment of sexual needs, psychological pressure, hierarchy between prisoners, and overcrowding conditions. Labuhan Deli Class I Detention Center experiences significant overcrowding with 1525 residents for a capacity of 500 people, which has the potential to trigger sexually deviant behavior. The purpose of this study is to determine the form of sexual deviant behavior of male inmates at the Class I Labuhan Deli State Detention Center and to determine efforts to control the sexual deviant behavior of male inmates. The method used in this research is descriptive qualitative, which examines thoroughly and in depth what is being studied using data collection techniques such as interviews, observations, and documentation studies. This research uses Abraham Maslow's Hierarchy of Needs Theory, which states that sexual needs are basic needs that must be fulfilled by every human being. The results of the study found that there were 6 prisoners involved in sexually deviant behavior in the detention center. The forms of sexual deviant behavior that occur in the Labuhan Deli Class I Detention Center are homosexuality and sexual practices using anal and oral. Factors that cause deviant behavior are the overcrowded conditions of the detention center and the unchanneled sexual needs of prisoners. Therefore, the efforts made to control the sexual deviant behavior of prisoners in the Labuhan Deli Detention Center are with a preemptive strategy, namely separating prisoners involved in sexual deviations and then recording them in the F register book, providing independent services and personality services, and conducting routine HIV screening. Keywords: Homosexuality; Deviant Behaviour; Prisoners